Pengaruh DAR Dan ROA Terhadap Kinerja Keuangan Perusahaan Industri Sub Sektor Otomotif Dan Komponen - Melia Lestari Tarigan; Aswin Akbar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study is to determine whether there is an effect of debt to total asset ratio (DAR) and return on assets (ROA) on the financial performance of the automotive and component sub-sector industrial companies listed on the Indonesia Stock Exchange (IDX). The population in this study are 12 industrial companies in the automotiveand component sub-sector listed on the Indonesia Stock Exchange (IDX) with a total sample of 36. The sampling method used is saturated sampling technique where the sample used is the entire population in this study. The independent variables used in this study are DAR and ROA, while the dependent variable is financial performance. This study uses annual data from 2019 to 2021 with the data analysis method used in this study is quantitative descriptive, while the analytical model used in this study is multiple linear regression analysis. Testing this hypothesis using the coefficient of determination (R2), partial test (t test) and simultaneous test (F test). The results of this study indicate that simultaneously DAR and ROA have a positive and significant effect on financial performance, in addition partially DAR and ROA have a significant and positive effect on financial performance.